Declaração de inidoneidade prevista na Lei nº 14.133/2021 como sanção regida pelo Direito Administrativo Sancionador - Moraes, Tassiane de Fatima (2024)
The purpose of this master's thesis is to address the declaration of unfitness set out in Law 14.133/2021 as an administrative sanction governed by the Sanctioner Administrative Right. It is a sanction governed by general national rules on bidding and administrative contracting. The study analyzes the administrative sanctioning act, from the perspective of the theory constructed in Administrative Law, under the specific prism of the sanctioning activity studied and examined by this field of Public Law. To this end, it discusses the Sanctioner Administrative Right, as well as the administrative sanctioning model, of which the declaration of unfitness is an integral part, having as its central object of the investigation the discipline instituted in the new Bidding and Administrative Contracts Law. The understanding of the subject leads to a study of the legal and regulatory evolution of the sanction of unfitness, as well as fundamental aspects of its sanctioning regime, including an analysis of its elements and assumptions (of existence and validity), as well as its effectiveness, examining the administrative sanctioning process, the disregard of legal personality, rehabilitation and the issues of consensusality and discretion in the sanctioning arrangement. It concludes with a comparison of sanctions with similar content in the Brazilian Sanctioner Administrative Right. To this end, a bibliographical and jurisprudential review was carried out on the topics, especially the declaration of unfit. Using the deductive method, we started with a general analysis of administrative sanctions and then evaluated those arising from tenders and contracts in the context of the new legislation. The results reveal the need to improve some points that are still unclear in the new legislation, such as certain infractions that remain open-ended. However, the progress made has been significant, outlining in detail some points of the sanction of declaration of unfit and the institutes that affect it, such as rehabilitation. The conclusion is that there is a need for regulation on the part of the entities on issues that have not yet been provided for in the law, such as aggravating and mitigating factors; as well as legislative changes on issues that are not in line with the national legal system, such as extending the sanction of a declaration of unfit to all entities of the federation